ANALYSIS OF RESEARCH SKILLS FOR HIGH SCHOOL STUDENTS ON BIOLOGY LEARNING - Moh Sarjana; Elzha Yulianingsih Haditia; Na’ilah Zhafirah; Evi Roviati (Master of Science Education Program, Postgraduate Program of Cenderawasih University, 2025)
Abstract: Research skills are important for students because they can help identify problems, collect sourcesof information, channel resources for the quality and relevance of research and produce effective solutionsto problem solving. This study was conducted in three different schools in the city and district of Cirebon.The three schools include SMA Negeri 1 Sumber, SMA Negeri 1 Ciwaringin and MAN 2 Kota Cirebon. Theresearch method used is descriptive qualitative. The results of this study indicate that students' research skillsin Cirebon need to be improved. It is recommended for SMA/MA Cirebon teachers to apply active andcollaborative learning methods, such as project-based learning or laboratory experiments, with the aim ofimproving students' research skills. It is hoped that these steps will contribute to the development of students'critical and analytical thinking skills, and foster independence in research.Keywords: Research skills, Laboratory, Critical thinking skills, Problem solving